Florida 4-H Livestock Market Animal Record Book - Nancy Johnson (EDIS)
4-H Livestock Market Animal Record Book (4H ASM 50) is an animal sciences record book for all members in this project area to keep record of their market animals. In EDIS this publication is DLN 4H 108. Visit the 4-H Youth Development Curriculum website for more information on related project materials.